2002
DOI: 10.1007/s00586-001-0361-y
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines and growth factors in the protruded intervertebral disc of the lumbar spine

Abstract: IntroductionThe pathogenetic mechanism of low back pain and nerve root damage in lumbar disc herniation is the subject of ongoing debate. In particular, given that the mechanicalischaemic hypothesis alone cannot explain the cause-effect relationship between disc degeneration and neurological impairment, a biochemical mechanism is likely to be involved. It has recently been demonstrated that the autologous nucleus pulposus can induce histological and functional changes in spinal nerve roots when applied epidura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
77
0
5

Year Published

2003
2003
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(83 citation statements)
references
References 33 publications
1
77
0
5
Order By: Relevance
“…IL-6 has multiple functions in a wide variety of biological processes, including the immune system, neuronal regulation, hematopoiesis, and inflammation (Gadient and Otten, 1997;Barnes et al, 2011). Relevant to this study are the findings that a protruded IVD was immunoreactive for IL-6 at a 4-fold higher intensity than normal tissue (Specchia et al, 2002). Therefore, this cytokine may have an important, but unknown, function in regulating cell function in IVD pathology.…”
Section: Discussionsupporting
confidence: 51%
“…IL-6 has multiple functions in a wide variety of biological processes, including the immune system, neuronal regulation, hematopoiesis, and inflammation (Gadient and Otten, 1997;Barnes et al, 2011). Relevant to this study are the findings that a protruded IVD was immunoreactive for IL-6 at a 4-fold higher intensity than normal tissue (Specchia et al, 2002). Therefore, this cytokine may have an important, but unknown, function in regulating cell function in IVD pathology.…”
Section: Discussionsupporting
confidence: 51%
“…The increased concentrations of these substances in the herniated disc tissue suggests that cytokines potentially have the ability to cause endoneural edema and nerve fiber demyelination. [21][22][23] Furthermore, cytokines excite nociceptors, which suggests that they may play a critical role in peripheral hyperalgesia and pain behavior. 24,25 Nonetheless, the potential involvement of these substances in disc herniation may be related to a local process.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that this growth factor is absent in control disc tissue [7,23]. However, in a recent biochemical tissue culture study on growth factors and inflammatory mediators in patients undergoing surgery for scoliosis, lumbar radiculopathy and discogenic pain, production of TGFb-1 was demonstrated both in control (scoliosis) and degenerate human disc tissues [2].…”
Section: Discussionmentioning
confidence: 99%